PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA KEJAHATAN PORNOGRAFI DUNIA MAYA (CYBERPORN): STUDI DI KEPOLISIAN DAERAH JAWA TIMUR - Yohanna Andriani Novivace Hermawan; Yana Indawati (Gapenas Publisher, 2023)
Cyberporn is a crime based on the internet. Cyberporn crime cases in East Java have increased significantly, but this has not been followed by optimal law enforcement. This phenomenon has resulted in cyberporn cases still occurring in East Java. This study aims to determine law enforcement against perpetrators of cyber pornography (cyberporn) crimes in the East Java Regional Police. The research method in this study is empirical juridical. Primary and secondary data were obtained through interviews with Officers and Bintara Unit 1 of the East Java Regional Police's Cyber Crime Sub-Directorate—qualitative descriptive analysis method. The results of this study show that law enforcement carried out by the Cyber Crime Directorate of Special Criminal Investigation for the East Java Regional Police has not run best because obstacles found in the implementation process, such as limited jurisdiction, ineffective coordination, delays in response and lack of awareness of the law and internet usage policies. Cyber Crime Directorate of Special Criminal Investigation for the East Java Regional Police can overcome these obstacles by making the best possible efforts